2015
DOI: 10.5937/skolbiz1-7899
|View full text |Cite
|
Sign up to set email alerts
|

Managing sustainable development of rural tourism in Vojvodina

Abstract: Ruralni turizam u Vojvodini je prepoznat kao faktor revitalizacije sela u cilju rešavanja ekonomskih i demografskih problema. Međutim, ruralni turizam još uvek nema jasno definisane elemente marketing miksa (proizvod, cena, promocija i distribucija), niti se njegov razvoj bazira na osnovama održivog razvoja. Korišćenjem SWOT analize, u radu je analiziran trenutni status ruralnog turizma u Vojvodini i dati su predlozi za prevazilaženje postojećih problema i adekvatnijeg korišćenja potencijala. Na osnovu analize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…At the beginning of the XXI century, in accordance with specific requirements of the users of tourist services, there are new forms of tourism developed, within which rural tourism occupies a significant place. Rural tourism is a form of tourism which includes all tourist activities which can take place in rural regions and which can be included in tourist offer of those regions (Njegovan et al, 2015). Rural tourism should be based in those areas which are rural in all aspects (Lane, 1994).…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the beginning of the XXI century, in accordance with specific requirements of the users of tourist services, there are new forms of tourism developed, within which rural tourism occupies a significant place. Rural tourism is a form of tourism which includes all tourist activities which can take place in rural regions and which can be included in tourist offer of those regions (Njegovan et al, 2015). Rural tourism should be based in those areas which are rural in all aspects (Lane, 1994).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Analysing the activities carried out so far by the provincial and republic-level authorities indicates that sources of financing directed towards developing tourism and stimulating entrepreneurial activities and capacities have existed. The AP of Vojvodina has recently been recognising the importance of developing tourism in Vojvodina, financially supporting the improvement of capacities of certain types of tourism (Njegovan, Demirović, & Radović, 2015). In In the measurement of item indicators, the highest rated indicators were those that concerned providing financial resources not conditioned by payments of high interest rates (Own finances, Grants and Subsidised loans).…”
Section: Economics Of Agriculturementioning
confidence: 99%
“…In this study, state policies were not found to be a highly influential factor. Still, previous experience points to an important role of the state in developing tourism in the territory of Vojvodina (Njegovan, Demirović, & Radović, 2015). The state, at the republic, provincial and local levels, should use its policies and instruments to give incentive to the development of sustainable tourism through entrepreneurial initiatives.…”
Section: Economics Of Agriculturementioning
confidence: 99%
“…However, rural tourism still does not have a clearly defined marketing mix of elements (product, price, promotion, and distribution), nor is its development based on the foundations of sustainable development (Njegovan et al, 2015).…”
Section: Vaso Jegdić Iva šKrbić Srđan Miloševićmentioning
confidence: 99%